Landslide hazards in the south of Kyrgyzstan and the main factors influencing their detection (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article provides information about the catastrophic processes of landslides in the south of Kyrgyzstan, which are caused by human casualties and serious damage to buildings and structures. Based on the results of the analyzed meteorological observations, the factors influencing the formation of landslides are named. It is concluded that landslide formation in the Kyrgyz Republic is mainly influenced by environmental factors, which further determines the specifics of preventive and protective measures.
Keywords: landslides; damage; factors and causes of landslides; exogenous geological processes; landslides in the south of the Kyrgyz Republic